A study of housing reconstruction and social cohesion among conflict and tsunami affected communities in Sri Lanka. Issue 5 (11th July 2016) - Haigh, Richard; Hettige, Siri; Sakalasuriya, Maheshika; Vickneswaran, G.; Weerasena, Lasantha Namal
Abstract : Purpose: The purpose of this paper is to critically analyse the role of housing reconstruction projects in post conflict and post tsunami Sri Lanka, and to discuss their implications on conflict prevention. Design/methodology/approach: Using four housing reconstruction projects in Batticaloa, Kilinochchi and Jaffna Districts, Sri Lanka, as case studies, and a novel methodological framework, the study explores the causal relations among the independent variables associated with housing reconstruction and dependent variables related to conflict prevention. The data, gathered from interviews and project reports, were analysed using propositions from a literature review, adopting a thematic analytical approach. Findings: This study finds that reconstruction has created new forms of conflicts and tensions for the people who came to live in the newly constructed houses. The hostile relations that existed among different ethnic groups during the conflict were continued, and to some extent, exacerbated by the reconstruction undertaken after the war. Practical implications: The study identifies causal relations among the independent variables associated with housing reconstruction and dependent variables related to conflict prevention, which can be used to inform physical reconstruction programmes after conflict. Originality/value: The research presents a novel methodological framework. The results reveal concerns in housing and infrastructure development that have implications for future research and practice in post conflict environments.